2018
DOI: 10.1098/rsbl.2018.0237
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing organic carbon accumulation in mangrove ecosystems

Abstract: There is growing interest in the capacity of mangrove ecosystems to sequester and store ‘blue carbon’. Here, we provide a synthesis of 66 dated sediment cores with previously calculated carbon accumulation rates in mangrove ecosystems to assess the effects of environmental and anthropogenic pressures. Conserved sedimentary environments were found to be within the range of the current global average for sediment accretion (approx. 2.5 mm yr –1 ) and carbon accumulation (approx. 160 g m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 22 publications
2
39
1
1
Order By: Relevance
“…The range in SAR of the studied mangroves (2.1–8.8 mm yr −1 ) was within the global average (7.7 mm yr −1 ; Arias‐Ortiz et al ), with SAR in the Piraquê‐Açu mangrove forests and tidal flats (8.8 mm yr −1 and 18.6 mm yr −1 , respectively) being close to the highest global accretion rates (Breithaupt et al ; Kusumaningtyas et al ; Wang et al ). SAR commonly increase from the low (tidal flats) to high‐intertidal (mangrove forests) in estuaries globally, although coastal geomorphology and forest structure may change in relation to regional patterns (Alongi et al , ; Sanders et al ; MacKenzie et al ; Perez et al ). The wide ranges in SAR between closely located estuaries indicated a notable variability in the regional sediment input to the systems studied.…”
Section: Discussionmentioning
confidence: 99%
“…The range in SAR of the studied mangroves (2.1–8.8 mm yr −1 ) was within the global average (7.7 mm yr −1 ; Arias‐Ortiz et al ), with SAR in the Piraquê‐Açu mangrove forests and tidal flats (8.8 mm yr −1 and 18.6 mm yr −1 , respectively) being close to the highest global accretion rates (Breithaupt et al ; Kusumaningtyas et al ; Wang et al ). SAR commonly increase from the low (tidal flats) to high‐intertidal (mangrove forests) in estuaries globally, although coastal geomorphology and forest structure may change in relation to regional patterns (Alongi et al , ; Sanders et al ; MacKenzie et al ; Perez et al ). The wide ranges in SAR between closely located estuaries indicated a notable variability in the regional sediment input to the systems studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies regarding the factors that influence carbon storage in the mangrove ecosystem are scarce, including which species and geography significantly impact carbon storage (McLeod et al 2011;Howard et al 2017). Few studies have observed the factors that influence carbon preservation in mangrove ecosystem (Matsui et al 2015;Weiss et al 2016;Martuti et al 2017;Asadi et al 2018;Pérez et al 2018;Gao et al 2019;Kida and Fujitake 2020). Findings of these studies showed that the influencing factors of carbon sequestration in the mangrove ecosystem were varied and complicated.…”
Section: Introductionmentioning
confidence: 99%
“…On the Ajuruteua Peninsula, in the state of Pará, for example, the patches of scrub mangrove forest are dominated almost entirely by A. germinans, which occupies the sites with the highest salinity and topography, forming a gradient from shrub-like trees to short mangrove trees [16]. These environmental drivers also have a direct influence on the production of biomass and carbon storage [17], with the trees distributing their nutritional resources as efficiently as possible in response to these conditions [18]. Studies of biomass production and carbon storage have focused on different types of mangrove forest around the world, including fringe [19], basin [20], riverine [21], and scrub [19] forest types, which have generated an ample range of estimates (~8-460 Mg ha -1 ), reflecting the diversity of environmental conditions.…”
Section: Introductionmentioning
confidence: 99%